"Sobri e ubriachi". Lo straniamento nel dibattito sulla poesia italiana degli anni Sessanta: ostranenie, Verfremdung, alienazione - Salvatore Spampinato (eSamizdat)
In this intervention we intend to develop a reasoning about the presence of the concept of Estrangement in the reflections of some Italian poets of the 1960s, taking into account the ambiguity of its possible reference to Viktor Šklovskij's ostranenie as well as to Verfremdung by Bertolt Brecht. First of all, we propose to discuss some of the most important critical contributions to the comparison between the Brechtian and Formalist categories, in order to understand their historical and substantial affinities and their peculiar differences. Subsequently, we intend to outline several ways through which the two different and similar concepts influence and mark the debate in the 1960s, on the Italian New Avant-garde and the literary representation of reality in the new capitalist society. This issue raises in a critical context heavily imbued with Marxism, but characterized by signs of openness towards semiotics and by a growing interest in Structuralism which will then be hegemonic at the end of the decade.